Perioperative Outcomes of Video-Assisted Thoracoscopic Surgery Versus Open Thoracotomy After Neoadjuvant Chemoimmunotherapy in Resectable NSCLC - Zhang, Baihua; Xiao, Qin; Xiao, Haifan; Wu, Jie; Yang, Desong; Tang, Jinming; Li, Xu; Wu, Zhining; Zhou, Yong; Wang, Wenxiang (Frontiers in Oncology, 2022)
Background: Neoadjuvant chemoimmunotherapy becomes more widespread in the treatment of NSCLC, but few studies have reported the details of surgical techniques and perioperative challenges following neoadjuvant chemoimmunotherapy until now. The primary aim of our study was to address the feasibility and safety of pulmonary resection after neoadjuvant chemoimmunotherapy via different surgical approaches, video-assisted thoracoscopic surgery (VATS) and open thoracotomy. Methods: Patients with an initial diagnosis of clinical stage IB-IIIB(T3-4N2) NSCLC, who received neoadjuvant chemoimmunotherapy and surgery between January 2019 and August 2021 were included. Patients were retrospectively divided into two groups (VATS, and thoracotomy), and differences in perioperative, oncological, and survival outcomes were compared. Results: In total, there were 131 NSCLC patients included. Surgery was delayed beyond 42 days in 21 patients (16.0%), and radical resection (R0) was achieved in 125 cases (95.4%). Lobectomy was the principal method of pulmonary resection (102 cases, 77.9%) and pneumonectomy was performed in 11 cases (8.4%). Postoperative complications within 30 d occurred in 28 patients (21.4%), and no 30-d mortality was recorded. There were 53 patients (38.5%) treated with VATS, and 78 (59.5%) with open thoracotomy. VATS could achieve similar definitive resection rates, postoperative recovery courses, comparable morbidities, and equivalent RFS rates(p>0.05), with the advantages of reduced operative time (160.1±40.4 vs 177.7±57.7 min, p=0.042), less intraoperative blood loss (149.8±57.9 vs 321.2±72.3 ml, p=0.021), and fewer ICU stays after surgery (3.8% vs 20.5%, p=0.006) compared with open thoracotomy. However, the mean number of total lymph nodes resected was lower in the VATS group (19.5 ±7.9 vs 23.0 ±8.1, p=0.013). More patients in the thoracotomy group received bronchial sleeve resection/bronchoplasty (53.8% vs 32.1%, p=0.014) and vascular sleeve resection/angioplasty (23.1% vs 3.8%, p=0.003). After propensity score matching (PSM) analysis, VATS still had the advantage of fewer ICU stays after surgery (2.3% vs. 20.5%, p=0.007) Conclusions: Our results have confirmed that pulmonary resection following neoadjuvant PD-1 inhibitors plus chemotherapy is safe and feasible. VATS could achieve similar safety, definitive surgical resection, postoperative recovery, and equivalent oncological efficacy as open thoracotomy, with the advantages of fewer ICU stays after surgery.